Effect of the Supplementation with Protected Fats in the Diet of Dairy Cows on The Quantity and Quality of Milk - Adela Marcu; Lavinia Stef; Calin Julean; Ioan Pet; Voichita Gherasim; Nicolae Pacala; Ion Valer Caraba; Dorel Dronca; Marioara Nicula Neagu; Vasile Rus; Ducu Sandu Stef (Scientific Papers Animal Science and Biotechnologies, 2023)
The objectives of this paper were to analyze studies on the effects of supplementation with protected fats in the diet of dairy cows on milk production and its chemical composition. Many fats can be used in the diet of dairy cows as sources of protected fatty acids. Adding of protected fats in the diet of dairy cows were significant effect on milk production and were influenced by some factors such as supplemental fat sources, the stage of lactation, dry matter intake. However, some authors reported an insignificant effect on milk production and the chemical composition of milk (fat, protein and lactose) as a result of supplementing the diet with protected fats. In other studies, have shown that the use of unsaturated fatty acids in the diet of dairy cows had effect on the biohydrogenation process in rumen and reduction of the total content of saturated fatty acids in milk. In this review, based on the works analyzed we can conclude that the diet supplemented with protected fats in dairy cows had effect on the quantity and quality of milk.